APPROACHES TO DETERMINING THE STAGES OF THE LANGUAGE TEACHING METHODS DEVELOPMENT IN WESTERN UKRAINE (1867-1939) - Bogdana Labinska (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2016)
The article under discussion focuses on scientific works, dedicated to the development of language teaching methods. We have analysed the criteria for singling out the stages of contemporary scholars' methods of development and created our own criteria regarding language teaching methods in Western Ukraine (1867-1939). According to the selected criteria, we have determined the basic stages of development methods on a particular territory, in a specific chronological framework: stage I - 1867-1890 - the emergence of the language teaching methods; stage II - 1890-1918 - the formation of foreign language teaching methods; stage III - 1918-1939 - further development of language teaching methods. These stages have been marked with certain innovative ideas of foreign language teaching approaches. They have also set certain scientific practice standards and theoretical postulates, preserving, at the same time, the teaching theories, concepts, approaches, principles, foreign language teaching methods, accepted by the professional community. Certain approaches to curricula development, in accordance with the peculiarities of each region, some principles of creating the educational materials, regarding the students' age and interests, are inherent to each phase of the development of Linguistic Didactics in Western Ukraine. In our studies, we have proved that grammar translation, textual translation, direct and mixed methods of foreign language teaching have been implemented in accordance with the characteristic features of the outlined area and within the fixed chronological frames. We have highlighted the provisions of foreign language teaching methods that have remained unchangeable in the process of foreign language teaching in Western Ukraine. The latter methods have acquired new features and emerged in foreign language teaching methods on Western Ukrainian territories during their implementation within a specified period of time.